Emergency imaging a practical guide - Baxter, Alexander B. (Thieme, 2016)
A comprehensive introduction to the clinical radiology of trauma and acute diseases, Emergency Imaging: A Practical Guide helps readers acquire the image interpretation skills necessary to care for patients with emergent conditions. This book is organized by anatomic region, and each of the eight sections has an introduction that includes an analytical approach and checklist, important anatomy, imaging techniques, and key differential diagnoses.